1994
DOI: 10.1182/blood.v83.5.1188.bloodjournal8351188
|View full text |Cite
|
Sign up to set email alerts
|

Flexible granulocyte colony-stimulating factor dosing in ovarian cancer patients who receive dose-intense taxol therapy

Abstract: As has been reported with other chemotherapeutic agents, evidence is emerging to suggest that increased taxol dose intensity is associated with improved therapeutic efficacy. Granulocyte colony-stimulating factor (G-CSF) effectively protects the bone marrow from taxol-induced neutropenia and allows for higher taxol dose administration. This report addresses the optimal use of G-CSF as a supportive agent for dose-intense taxol therapy. Forty-seven patients were evaluated. Each ovarian cancer patient received ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…27 Early studies of paclitaxel in ovarian carcinoma identified neutropenia as the most common dose limiting toxicity. 27,28 We demonstrated a higher RR to paclitaxel at a dose of 250 mg/m 2 , requiring growth factor support due to the frequency of grade 3 and 4 neutropenia. [27][28][29] The doses and schedules used today in ovarian carcinoma were chosen in large part to minimize growth factor supplementation requirements; similar studies may be useful to further understand prexasertib.…”
Section: Discussionmentioning
confidence: 90%
“…27 Early studies of paclitaxel in ovarian carcinoma identified neutropenia as the most common dose limiting toxicity. 27,28 We demonstrated a higher RR to paclitaxel at a dose of 250 mg/m 2 , requiring growth factor support due to the frequency of grade 3 and 4 neutropenia. [27][28][29] The doses and schedules used today in ovarian carcinoma were chosen in large part to minimize growth factor supplementation requirements; similar studies may be useful to further understand prexasertib.…”
Section: Discussionmentioning
confidence: 90%